Hubungan Keterpaparan Media Massa dan Peran Orangtua Terhadap Perilaku Seksual Pada Remaja di SMP APekanbaru Tahun 2017 - Irmawati Irmawati; Lidia Fitri; Afritayeni Afritayeni (STIKes Hang Tuah Pekanbaru, 2020)
Demographic Survey of Health Indonesia (SDKI) 2012 increase on teenagers aged 15-19 years, where young men (4.5%) and female teenagers (0.7%) they have had premarital sex. The results of research the Ministry of Communication and Informatics of the year 2014, at the age of 10-19 years with the population reach to 43.5 million obtained that consist of 52% find pornography content through advertising/ site that is not suspicious and consists of 14% access pornographic sites voluntarily. Based on the initial survey in SMP A Pekanbaru against ten people students through of 7 from 10 that found they already courtship, the most of them holding hands and embrace the type of opponents. The purpose of this research is to know the relationship between establishment of mass media and the role of parents for sexual behavior in adolescents in SMP A Pekanbaru 2017. The type of research that is analytically quantitatively with cross sectional design. Sampling techniques namely stratified random sampling that consist of 158 respondents. Based on the results of chi square test obtained there is any the relationship between establishment of the mass media and sexual behavior with p value 0,000 < 0.05 and they were not the existence of the courtship between the role of parents and sexual behavior with p value 0,759 > 0.05. The results of the study showed the majority of respondents were establishment to the mass media that consist of (82,3%) and the majority of the parents role that consist of (91.1%) and the majority of respondents at risk from sexual behavior that consist of (27.8%). The school should work together with health agencies in provide information about reproductive health and work together with the BKKBN in create a program of the Center of Information and Counselling Adolescents (PIK-R).